(Ba0.5Sr0.5)(Co0.8Fe0.2)O3-δ Thin Films Derived by Metal-Organic Deposition: Preparation of Nanoscaled Surface Modifications and Electrochemical Characterization. Issue 3 (13th January 2016) - Asano, Koichi; Niedrig, Christian; Menesklou, Wolfgang; Wagner, Stefan F.; Ivers-Tiffée, Ellen
Abstract : In this study, nanoscaled (Ba0.5 Sr0.5 )(Co0.8 Fe0.2 )O3-δ (BSCF) thin films (with thicknesses below 100 nm) have been successfully deposited onto NdGaO3 single crystal substrates using a metal-organic deposition (MOD) method. In contrast to physical vapor deposition techniques, e.g. pulsed-laser deposition or magnetron sputtering, BSCF thin films formed by an MOD method provide the possibility to custom-tailor the surface morphology by subsequent annealing treatments, enabling selective surface nanostructuring. Changes of surface area or phase composition (cubic, hexagonal BSCF, others) are expected to affect the catalytic activity of oxygen-transport membranes. A study of surface morphologies achieved by a variation of the post-deposition thermal treatment is presented. The electrical properties of selected MOD thin films were determined up to 800°C and compared to data for epitaxial BSCF thin films and bulk samples. Lastly, oxygen exchange kinetics were investigated by electrical conductivity relaxation measurements analyzed, in the frequency domain, yielding oxygen surface exchange coefficients k δ ( T ) between 400…600°C.